Pemanfaatan Website Dalam Mengembangkan Kreatifitas Siswa Di Dunia Usaha - Ria Eka Sari; Alfa Saleh; M. Rizki Afandi (LPPM STIKOM Tunas Bangsa, 2021)
In this increasingly developing era, the internet is a medium used as a means of communication which has gradually eliminated communication media such as telephone or SMS (short message send). This is due to what has been proven that in everyday life at this time, humans are attached to a network. The development of the internet has also supported the use of computers in education. The internet can be accessed and used for various purposes, by anyone, anywhere, anytime. Various kinds of internet technology can be used, one of which is the World Wide Web (or hereinafter referred to as the